The influence of 4-week eccentric Nordic hamstring exercise training on postural balance and muscle strength: A randomized controlled trial. - Magdalena Podczarska-Głowacka; Ewelina Perzanowska; Katarzyna Krasowska; Zuzanna Trapik; Agata Kalkowska; Sebastian Klich (PLoS ONE, 2025)
This study aimed to determine the impact of a 4-week Nordic Hamstrings Exercise (NHE) eccentric training program on postural balance in static and dynamic conditions, focusing on the dominant leg. This study involved thirty-two recreationally active individuals, randomly divided into two groups: Nordic Exercise training (NHE Group; n = 16) and the matched-control group (CON Group; n = 16). The NHE Group performed Nordic hamstring exercise training for 4 weeks, during which the volunteer exercised 3 times a week for 3 sets, each set consisting of 3 repetitions of NHE. Postural balance was assessed using three tests: static balance on a stable platform with eyes closed, dynamic balance on an unstable platform for both legs and dynamic balance on an unstable platform for the dominant leg. Three indices were measured using the Biodex Stability System: Anterior-Posterior Stability Index (APSI), Medio-Lateral Stability Index (MLSI), and Overall Stability Index 1 (OSI). The NHE group significantly improved balance on a stable platform with eyes closed compared to baseline (p ≤ 0.001) and on unstable platforms compared to both baseline and the control group (p ≤ 0.001). Both groups improved knee strength, but the NHE group showed significantly greater improvements (p ≤ 0.001 for NHE, p ≤ 0.04 for control). Strong positive correlations (r = 0.5 to 0.7) were found between stability measures, suggesting shared underlying mechanisms influencing balance (p < 0.01). A 4-week NHE training protocol effectively improves postural balance and performance in athletes. Measuring postural control is valuable for assessing neuromuscular function and injury prevention in athletic populations. This study suggests that eccentric NHE exercises may improve athlete balance, reduce hamstring injury risk, and decrease the need for rehabilitation by activating posterior thigh muscles.